FACTORS AFFECTING THE POPULATION MOBILITY WARD IN THE SUNGAI KERJAN DISTRICT BUNGO DANI REGENCY BUNGO JAMBI PROVINCE - ANDIKA SARI, RINI; Erita, M.Pd, Yeni; Eka Putri, M.Si, Rozana (STKIP PGRI Sumbar, 2014)
ABSTRACT This study aims to obtain, process, analyze, and discuss data on factors that influence population mobility in the Village Kerjan River Dani Kerjan Bungo Bungo District of Jambi Province .This type of research is Descriptive Correlational . The populations in this study were all residents who do mobility of the population in 1693 amounted Kerjan River Village KK. To determine the sample size is proportional random sampling with 25 % proportions. Number of sample respondents by 41 people. Data collection techniques used were in the form of questionnaires and interviews .The results of this study indicate that the presence of 1. Influence significant narrowing of employment between the mobility of the population of 13.3 % Kerjan River in the Village District of Dani Bungo Bungo Jambi, 2. Significant influence on mobility between natural disasters population of 12.2 % Kerjan River in the Village District of Bungo Bungo Jambi Dani , 3 . Presence of significant effect of disease on a population of 39.4 % mobility in the Village River District of Bunga Dani Kerjan Jambi Province.